2015
DOI: 10.1111/jgh.12922
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of endoscopic ultrasound‐guided sampling using core biopsy needle as a percutaneous biopsy rescue for diagnosis of solid liver mass: Combined histological‐cytological analysis

Abstract: EUS-FNB with core biopsy needle for solid liver mass may be helpful in the management of patients who are unable to diagnose using percutaneous liver biopsy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 21 publications
1
39
1
Order By: Relevance
“…However, fewer passes were required to obtain the pathological diagnosis in the core biopsy needle group (1.0 vs 2.0). Lee et al also reported the usefulness of EUS‐guided sampling for solid liver masses by using core biopsy needle . We had expanded the study to evaluate molecular test from EUS‐guided samples for liver masses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fewer passes were required to obtain the pathological diagnosis in the core biopsy needle group (1.0 vs 2.0). Lee et al also reported the usefulness of EUS‐guided sampling for solid liver masses by using core biopsy needle . We had expanded the study to evaluate molecular test from EUS‐guided samples for liver masses.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al also reported the usefulness of EUS-guided sampling for solid liver masses by using core biopsy needle. 22 We had expanded the study to evaluate molecular test from EUS-guided samples for liver masses. In this study, the core biopsy needle was used with the expectation of obtaining sufficient samples for cytohistology and KRAS mutation analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Cytological diagnoses were classified as positive for malignancy, suspicious for malignancy, atypical, negative, and inadequate. [9] Cytological diagnoses classified as positive for malignancy and suspicious for malignancy were considered malignant. [10] Cytological examination that was diagnostic for malignancy was considered the definitive diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, EUS biopsies are preferable. 216 Transvenous biopsies from the internal jugular vein through the vena cava are reserved for lesions adjacent to the venous system or where there is significant bleeding risk or ascites. 217 Similarly, FNAB, CNB, and occasionally microforceps 218 modes are used depending on the application.…”
Section: Livermentioning
confidence: 99%